2017
DOI: 10.1021/acs.nanolett.7b03742
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Stability in Axial InAs–InP Nanowire Heterostructures with Atomically Sharp Interfaces

Abstract: The possibility to expand the range of material combinations in defect-free heterostructures is one of the main motivations for the great interest in semiconductor nanowires. However, most axial nanowire heterostructures suffer from interface compositional gradients and kink formation, as a consequence of nanoparticle-nanowire interactions during the metal-assisted growth. Understanding such interactions and how they affect the growth mode is fundamental to achieve a full control over the morphology and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 61 publications
0
45
0
1
Order By: Relevance
“…The metallorganic pressures were 0.3, 1.0, and 4.0 Torr for TMIn, TBAs, and TBP, respectively. These growth conditions ensure to achieve InAs/InP NW heterostructures with straight morphology, constant diameter, wurtzite crystal structure and atomically sharp interfaces [56,72]. InAs/InP and InP/InAs interfaces where realized without any interruption by switching the group V precursors.…”
mentioning
confidence: 99%
“…The metallorganic pressures were 0.3, 1.0, and 4.0 Torr for TMIn, TBAs, and TBP, respectively. These growth conditions ensure to achieve InAs/InP NW heterostructures with straight morphology, constant diameter, wurtzite crystal structure and atomically sharp interfaces [56,72]. InAs/InP and InP/InAs interfaces where realized without any interruption by switching the group V precursors.…”
mentioning
confidence: 99%
“…Отдельного внимания исследований последних лет удостоился рост ННК тройного состава III−V как простейшего варианта гетероструктур [1,11]. Выяснилось, что качество гетероструктур лимитируется растворимостью элементов в капле: во-первых, растворенные элементы могут приводить к размыванию гетероперехода [12]; во-вторых, различие в растворимости элементов может приводить к смещению капли и изменению направления роста [13]. Наименее подверженной этим недостаткам является система Ga(As, P) [8,14].…”
Section: полупроводниковыеunclassified
“…Interestingly, for nanowires grown at 450°C, the TESn addition reduces the growth rate. To understand this, we note that the catalyst plays a crucial role in nanowires growth, 25,43,44 and the chemical potential difference between the catalyst and underlying nanowire (the supersaturation in the catalyst) is the key driving force for axial growth. 45 In our previous study, 46 we found that when Sn is incorporated into the Au catalysts, it competes with Ga to form Au−Ga−Sn alloy droplets, resulting in a reduced Ga concentration in the catalysts and in turn lowers the catalyst supersaturation level, causing lowered nanowire growth rate.…”
Section: And D Of Figures 3 and Parts I And J Ofmentioning
confidence: 99%